Applying The Carbon Scope Framework for Decarbonisation in a South African High Alloy Foundry - Kabasele, J.K.; Nyembwe, K.D.; Mashinini, P.M. (The South African Journal of Industrial Engineering, 2025)
Carbon emissions constitute a growing concern for South Africa’s manufacturing sector, particularly the foundry industry. Despite national commitments to achieve net-zero emissions by 2050 and the implementation of carbon tax regulations, many foundries have been slow to adopt effective decarbonisation measures. This study quantifies the carbon footprint of a high-alloy castings foundry using Scope 1, 2, and 3 methodologies, converting data from molten metal production, electricity use, logistics fuel, and staff transport into CO₂-equivalent emissions. Results showed that electricity was the dominant contributor at 83.7% (27.6–161.9 tCO₂), followed by gas at 13.4% (10.25–25.86 tCO₂), diesel at 2.3% (0.51–4.48 tCO₂), and petrol at 0.6% (<1.11 tCO₂). The study recommends adopting low-carbon fuels, automating temperature controls, implementing energy-management systems, integrating renewable energy for Scope 1 and 2 reductions, and transitioning to electric vehicles with improved logistics for Scope 3. These data-driven strategies support both national and global climate goals while promoting more sustainable foundry operations.